Pengaruh Firm Growth, Firm Size, Profitability, Managerial Ownership dan Institutional Ownership Terhadap Corporate Social Responsibility Disclosure (CSRD) - Nadhira Putri Zahrani; Triyono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Corporate social responsibility (CSR) is a company's obligation to consider the social and environmental impacts arising from its business activities, thereby encouraging ethical practices and responsible corporate behavior. This study aims to analyze the effect of firm growth, firm size, profitability, managerial ownership and institutional ownership on corporate social responsibility disclosure in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023.This study uses purposive sampling method in sample selection, with a total of 63 companies that meet the criteria as research objects. The analysis technique used is multiple linear regression. The results showed that firm size has an effect on CSRD, while firm size, profitability, managerial ownership and institutional ownership have no effect on CSRD